2023
DOI: 10.1002/pmic.202300202
|View full text |Cite
|
Sign up to set email alerts
|

A top‐down proteomic approach reveals a salivary protein profile able to classify Parkinson's disease with respect to Alzheimer's disease patients and to healthy controls

Abstract: Parkinson's disease (PD) is a complex neurodegenerative disease with motor and non‐motor symptoms. Diagnosis is complicated by lack of reliable biomarkers. To individuate peptides and/or proteins with diagnostic potential for early diagnosis, severity and discrimination from similar pathologies, the salivary proteome in 36 PD patients was investigated in comparison with 36 healthy controls (HC) and 35 Alzheimer's disease (AD) patients. A top‐down platform based on HPLC‐ESI‐IT‐MS allowed characterizing and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 103 publications
0
1
0
Order By: Relevance
“…In a recent study, Contini et al [46] enrolled 36 patients affected by PD, 36 healthy controls, and 35 AD patients (13 in moderate and 22 in mild disease stage). Using a proteomic approach, significant differences between various compounds in diagnostic groups were observed.…”
Section: Metabolomics and Proteomics Panel Studiesmentioning
confidence: 99%
“…In a recent study, Contini et al [46] enrolled 36 patients affected by PD, 36 healthy controls, and 35 AD patients (13 in moderate and 22 in mild disease stage). Using a proteomic approach, significant differences between various compounds in diagnostic groups were observed.…”
Section: Metabolomics and Proteomics Panel Studiesmentioning
confidence: 99%
“…Interestingly, thymosin β4 correlated positively, while statherin 2P negatively, with olfactory function and odor identification. Moreover, α-defensin 3 showed a negative correlation with the Unified Parkinson's Disease Rating Scale (UPDRS III) [59].…”
Section: Metabolomic and Proteomic Studiesmentioning
confidence: 99%
“…For instance, excessively nitrated ATP synthase F1 subunit alpha (ATP5F1A) is detected not only in postmortem tissue of AD patients [ 211 ] but also the blood cells of AD patients [ 212 ], suggesting nitrated ATP5F1A as a robust biomarker for AD. Interestingly, it has recently been shown that salivary protein profiling allows to distinguish PD and AD from controls, suggesting that proteins from saliva may be used in the future as another non-invasive and easily accessible source of biomarkers for NDDs diagnosis [ 239 ]; however, whether redox-PTMs would be preserved in salivary samples has yet to be explored. The quantification of redox-PTMs in bodily fluids, such as CSF or blood, remains technically challenging, as discussed in Section 3.2 ; therefore, strict methodological workflows would have to be developed to reduce technical artefacts being introduced [ 240 ].…”
Section: Future Directionsmentioning
confidence: 99%